Orb Weavers, Neoscona crucifera (Lucas 1839) and Neoscona domiciliorun (Hentz) (Arachnidae: Araneae: Araneidae) - Glavis B. Edwards, Jr. (EDIS)
Neoscona crucifera (Lucas 1839) and N. domiciliorum (Hentz 1847) are common and conspicuous members of the moist woodland communities in much of Florida. These spiders are beneficial, consuming a variety of insects. Although typically nocturnal throughout most of their life spans, adult females can be found sitting head down in the hubs of their webs during daylight hours of the fall season. Bites from these spiders are not known to cause serious effects to humans. This document is EENY-316 (originally published as DPI Entomology Circular 266), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.